Method for calculating the operating life of a steam pipe with a creep-fatigue crack near a weld joint - Dolinska, Iryna; Palash, Roman (Lviv Politechnic Publishing House, 2018)
A method for determining the period of sub-critical growth of a semielliptical creep-fatigue crack in the internal surface of a pipe wall of the steam pipeline is proposed. The crack is located near the ring weld in the field of residual stresses in the heat-affected zone. The dependence of the residual resource of the pipe of a steam pipeline with the weld joint on the location of the centre of the crack relative to the axis of the weld is ascertained.
Keywords: welded joint; steam pipeline; creep-fatigue crack; residual resource; period of subcritical growth of the crack